Strategies applied by accommodation service business in west sumatera to overcome the crisis of covid-19 pandemic - Sari, Rini Eka; Yanita, Novi (Journal of Business on Hospitality and Tourism, 2022)
This research aims to formulate strategies applied by accommodation service providers in West Sumatra in coping with the Covid-19 pandemic. The limitation in the mobilization or traveling that was imposed to break the chain of Covid-19 infection had brought the accommodation services on its knees in all regions including West Sumatra. Strategies formulated by means of SWOT (Strength, Weakness, Opportunity, Threat) analysis; by minimizing the weaknesses and threat, and boosting existing strength and opportunities. The gathering of research data was conducted through interviews with several stakeholders in the acommodation services business by applying purposive sampling method. The gathered data was then descriptively analysed by considering the strength, weakness, opportunity, and threat owned by the accommodation services in West Sumatra in order to formulate strategies in coping with the Covid-19 pandemic. The results of the research indicated that several strategies were applicable for implementation by the accommodation services in West Sumatra, i.e. the short, medium, and long-term strategies for the sustainability of the business.